Sistem Akuntansi Penjualan Kredit dan Pengendalian Intern Piutang Tak Tertagih Pada Koperasi Di SMA 12 Kota Padang - Angraini, Sisca Dian; Ananda, Febryandhie (Universitas Dharma Andalas, 2024)
A company in order to run well and achieve goals must exercise internal control. Internal control of bad debts is an activity carried out by the company that aims to protect company assets, produce accurate information and ensure compliance with policies made by management so as to prevent bad debts. This study aims to determine the effect of the credit sales accounting system on the internal control of bad debts in cooperatives at SMA N 12 Padang. The type of research is quantitative, the population of this study is all employees and active members in the SMA N 12 Padang cooperative as many as 42 people using total sampling techniques. Research measuring instruments using Likert scale questionnaires and data analysis using simple linear regression tests. Data processing using the SPSS program. The results showed that the regression coefficient value of the credit sales accounting system was 0.616 and the >calculated value of the ttable was 6.909>2.021, meaning Ha was accepted and H0 was rejected. The conclusion is that there is an influence of the credit sales accounting system on the internal control of bad debts in cooperatives at SMA N 12 Padang.